Evaluation of Physicochemical Properties and Antioxidant Activity of Polyphenol-Rich Cacao Bean Extract Through Water Blanching - Indiarto, Rossi; Pranoto, Yudi; Santoso, Umar; Supriyanto (Pakistan Journal of Nutrition, 2019)
Background and Objective: The activity of the polyphenol oxidase enzyme during fermentation and drying causes a decrease in the polyphenol and flavonoid content of cacao beans. Blanching is important to inactivate the enzyme. This study aimed to evaluate the physicochemical properties and antioxidant activity of cacao bean extract in order to obtain a polyphenol-rich cacao extract. Materials and Methods: Unfermented and fermented cacao beans were blanched using water at 95°C ±2°C for 1, 3, 5 and 7 min. The process was then followed with drying and defatting using n-hexane and completed with extraction of polyphenol compounds using 80% ethanol. The blanched cacao beans were analyzed in terms of polyphenol oxidase enzyme activity and color, while the extracts of dried cacao beans were analyzed in terms of the relative activity of polyphenol oxidase, color, total polyphenol content, total flavonoid content, radical scavenging activity using DPPH, ferrous ion (Fe2+) chelating activity and the presence of functional groups using fourier transform infrared (FTIR). Results: Blanching unfermented cacao beans at 95°C for 5 min reduced the relative activity of polyphenol oxidase by >99%, maintained the purple color of the unfermented cacao beans and produced the highest content of polyphenols and flavonoids. Five minute blanching also increased antioxidant activity compared to the activity of unblanched cacao beans. The process of fermentation and hot air drying had a significant effect (p0.05) on Fe2+ chelating activity in unblanched cacao beans. Total polyphenol and flavonoid contents were strongly correlated with DPPH antioxidant activity but were not correlated with Fe2+ chelating activity. Conclusion: Blanching unfermented cacao beans with hot water for 5 min at 95°C was shown to increase the free radical scavenging activity by deactivating the polyphenol oxidase enzyme and thereby increasing the total polyphenol content.